Fine-Tuning of hemB Using CRISPRi for Increasing 5-Aminolevulinic Acid Production in Escherichia coli - Su, Tianyuan; Guo, Qi; Zheng, Yi; Liang, Quanfeng; Wang, Qian; Qi, Qingsheng (Frontiers in Microbiology, 2019)
5-aminolevulinic acid (5-ALA) is an important metabolic intermediate in the biosynthesis of heme and has been broadly applied in medicine, agriculture, and organic synthesis. Comparing with the chemical synthesis methods, microbial fermentation of ALA has significant economic and environmental advantages. However, the heme biosynthesis pathway downstream of ALA is essential for cell survival, so it cannot be completely blocked. In this work, we fine-tuned the expression of HemB, the key enzyme involved in heme biosynthesis, using CRISPR interference (CRISPRi), and investigated its effect on promoting ALA accumulation. The activity of HemB was down-regulated by 15%, 19%, 33%, 36%, 71%, and 80% respectively with six CRISPRi sites targeting various regions of hemB. ALA accumulation in these hemB weakened strains was varied from 90.2% to 493.1% compared to that of the original strain. This work provided new insights into fine-tuning of heme biosynthesis pathway for promoting ALA production.